PELUANG DAN TANTANGAN MODEL BISNIS SYARIAH DI ERA DIGITAL - Alviansyah Fahrizatul Iman; Dewi Sartika; Salma Miranti; Tazila Erisyavanny; Muhammad Tegar; M. Alfa Razid; Reja Ahmad Patoni (ICONS: Islamic Economics Journal, 2025)
The sharia business model is a business system based on Islamic values such as justice, honesty, and social responsibility. In the digital era, this model has undergone significant transformation due to advances in information technology that have changed patterns of business interaction and transactions. Indonesia, as the country with the largest Muslim population, has great potential to develop a digital sharia economy, yet still faces several challenges such as low digital sharia literacy, unadaptive regulations, and limited human resources. This study uses a descriptive qualitative approach with the aim of identifying opportunities and challenges in developing sharia business models in the digital era. The results show that digitalization offers great potential for strengthening the sharia economy, but it must be supported by increased literacy, innovation-friendly regulations, and the development of competent human resources so that sharia businesses can grow sustainably and remain competitive in the digital age.